Liquid crystal composition with low viscosity and high birefringence

Through the design of meta-fluorine replacing isothiocyanate liquid crystal compounds, the problem of high rotational viscosity and viscoelastic coefficient of liquid crystal materials in the microwave frequency band is solved, high birefringence and low viscosity are achieved, and the response speed of liquid crystal devices is improved. and clear points, suitable for LCD optical and high-frequency microwave applications.

CN119144346APending Publication Date: 2024-12-17XIAN MODERN CHEM RES INST
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310713943.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-16
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing liquid crystal materials have relatively high rotational viscosity and large viscoelastic coefficient in the microwave frequency band, which is difficult to meet the performance requirements of liquid crystal optical components in response time and birefringence, especially in microwave and terahertz communication, optical communication and other fields. .

Method used

Using isothiocyanate-based liquid crystal compounds replaced by meta-fluorine, the liquid crystal composition with low rotational viscosity, high birefringence, and low viscoelastic coefficient are designed by adjusting the position of fluorine atoms in the molecular structure, including the first of the specific structures. One component, the second component, the third component and the fourth component, and a hindered phenolic antioxidant or hindered amine light stabilizer and chiral additive may be added.

Benefits of technology

The birefringence of the liquid crystal composition is improved, the rotational viscosity and viscoelastic coefficient are reduced, and the response speed and clear points of the liquid crystal device are enhanced. It is suitable for liquid crystal optical devices and high-frequency microwave components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144346A_ABST
    Figure CN119144346A_ABST
Patent Text Reader

Abstract

The invention discloses a liquid crystal composition with low viscosity and high birefringence. The liquid crystal composition disclosed by the invention comprises 60-100% by mass of a compound as shown in a general formula I as a first component. In a further scheme, the compound also comprises the following components in percentage by mass: 0-30% of a compound as shown in a structural general formula II, 0-30% of a compound as shown in a structural general formula III or / and 0-30% of a compound as shown in a structural general formula IV. According to the liquid crystal composition, the birefringence is larger than 0.39 at the temperature of 25 DEG C and the wavelength of 589 nm, and the rotary viscosity is smaller than 180 mPa.s. The liquid crystal compound has the advantages of low viscosity, high birefringence, low viscoelastic coefficient and wide nematic phase temperature interval. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field The invention belongs to the technical field of liquid crystal materials, and in particular relates to a liquid crystal composition with low viscosity and high birefringence. Background Art Liquid crystal materials are widely used in liquid crystal optical elements such as optoelectronic display devices, for example, in various LCD televisions, desktop LCD monitors, mobile display terminals, etc. In recent years, with the continuous development of microwave and terahertz communication, optical communication, laser phased array and other technologies, there is an urgent need for liquid crystal materials with low viscosity and high birefringence. In the microwave working band (1-100GHz), the higher the birefringence (Δn) of the liquid crystal, the greater its dielectric tunability in the microwave frequency band. The response time of liquid crystal is a key indicator affecting the performance of the device, and it is hoped that the response time is as short as possible. In liquid crystal optical elements such as optical communications and laser phased arrays, the application of liquid crystal materials with high birefringence (Δn) can reduce the thickness of the liquid crystal layer and shorten the response time. Another effective solution is to use liquid crystal materials with as low viscosity and low viscoelastic coefficient as possible. The response speed of the liquid crystal mainly depends on the cell thickness (d) of the liquid crystal device, the rotational viscosity (γ1) of the liquid crystal material, and the elastic constant (K 11 ), as follows: Where: t on is the on-state (power-on) response time, t off is the off-state (power-off) response time; V th is the threshold voltage of the liquid crystal, V is the external driving voltage; when the cell thickness d is fixed, to improve the response speed of the liquid crystal device, the liquid crystal material must have low rotational viscosity (γ1), large elastic constant (K 11 ), that is, low viscoelastic coefficient (γ1 / K 11 ). Therefore, there is an urgent need to develop liquid crystal materials that have low viscosity, high birefringence characteristics, and low viscoelastic coefficient. Liquid crystal molecules containing isothiocyanate groups (-NCS) have advantages such as higher birefringence, lower viscosity, and higher resistivity than molecules containing cyano groups (-CN), and have better application prospects. Liquid crystals containing isothiocyanate groups (-NCS) are prone to produce smectic phases. However, most of the liquid crystal materials currently used in optoelectronic devices are nematic liquid crystal materials. Therefore, in order to improve the phase properties of isothiocyanate (-NCS) liquid crystals and obtain nematic liquid crystal phase characteristics, lateral substituents can be introduced in the direction of the short axis of the molecule. In particular, isothiocyanate liquid crystal compounds with fluorine atoms introduced laterally into the molecule have obtained a wider nematic liquid crystal temperature range. The fluorine-substituted isothiocyanate liquid crystal compounds and their compositions disclosed in existing documents are all based on liquid crystal compounds in which one or two fluorine atoms are introduced at the ortho position of the isothiocyanate group on the benzene ring. For example, the liquid crystal compounds and compositions disclosed in the following documents:

[0001] Catanescu CO, Wu ST, Chien LC. Tailoring the physical properties of somehigh birefringence isothiocyanato-based liquid crystals. Liq Cryst. 2004; 31:541-555.

[0002] Parish A, Gauza S, Wu ST, Dziaduszek J, Dabrowski R. New fluorinatedterphenyl isothiocyanate liquid crystals. Liq Cryst. 2008; 35:79-86.

[0003] Song Q,Gauza S,Xianyu H,Wu ST,Liao YM,Chang CY,Hsu C S.Highbirefringence lateral difluoro phenyl tolane liquid crystals.Liq Cryst.2010;37:139–147.

[0004] R,Kula P,Herman J.High birefringence liquidcrystals.Crystals.2013;3(3):443-482. CN105368465A, CN107955630A and the like disclose liquid crystal compositions containing ortho-fluorine-substituted isothiocyanate groups (-NCS), and applications thereof in the microwave frequency band. However, the existing liquid crystal compositions based on ortho-fluorine-substituted isothiocyanate groups (-NCS) still have problems such as relatively high rotational viscosity and high viscoelastic coefficient. In order to further meet the working performance requirements of liquid crystal optical, microwave and other components, it is urgently necessary to research and develop new liquid crystal compositions with low viscosity, high birefringence, low viscoelastic coefficient and wide nematic phase temperature range. Summary of the invention In order to overcome the defects or shortcomings in the background technology, the present invention provides a new liquid crystal composition with low viscosity, high birefringence and low viscoelastic coefficient. In order to achieve the above-mentioned task, the liquid crystal composition of the present invention comprises a compound represented by the general structural formula I as the first component: Wherein: R is an alkyl group having 1 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, or a 3-butenyl group; The mass percentage of the first component in the liquid crystal composition is 60-100%. Furthermore, it is preferred that the mass percentage of the first component is 70 to 90%. An optional solution is that the liquid crystal composition of the present invention further comprises a compound represented by the general structural formula II as a second component: Wherein: R1 is an alkyl group having 1 to 7 carbon atoms, an alkoxy group having 1 to 7 carbon atoms, or an alkenyl group having 2 to 5 carbon atoms; The mass percentage of the second component in the liquid crystal composition of the present invention is 0 to 30%, and preferably 5 to 25%. An optional solution is that the liquid crystal composition of the present invention further comprises a compound represented by the general structural formula III as a third component: Wherein: R2 is an alkyl group having 1 to 7 carbon atoms or an alkoxy group having 1 to 7 carbon atoms; Ring A is a cyclohexane ring or a benzene ring. The mass percentage of the third component is 0-30%. Furthermore, it is preferred that the mass percentage of the third component is 5 to 25%. An optional solution is that the liquid crystal composition of the present invention further comprises a compound represented by the general structural formula IV as a fourth component: Wherein: R3 is an alkyl group with 1 to 7 carbon atoms or an alkoxy group with 1 to 7 carbon atoms; Ring A is a cyclohexane or a benzene ring; n=0 or 1; the mass percentage of the fourth component is 0 to 30%. Furthermore, the mass percentage of the fourth component is preferably 5 to 25%. Further, the fourth component of the present invention is preferably selected from the following components: The percentage is 0 to 30%. In a further embodiment, the liquid crystal composition of the present invention may further comprise 0.001% to 1% of an additive, wherein the additive is selected from a hindered phenol antioxidant and / or a hindered amine light stabilizer, etc. The hindered phenol antioxidant is preferably selected from the following structures: Here, R' is an alkyl group having 1 to 9 carbon atoms or an alkoxy group having 1 to 9 carbon atoms. The hindered amine light stabilizer is preferably selected from the following structures: In a preferred embodiment, the mass percentage of the additive added to the liquid crystal composition is 0.01% to 0.5%, more preferably 0.02% to 0.2%. In some further embodiments, the liquid crystal composition of the present invention may further comprise one or more chiral additives, with a content of 0.01% to 1%, preferably 0.1% to 0.5%. The chiral additives are preferably selected from the following structures: Wherein R" is an alkyl group or an alkoxy group having 1 to 9 carbon atoms. The liquid crystal composition of the present invention has a birefringence of greater than 0.39 at 25° C. and 589 nm, a rotational viscosity of less than 180 mPa·s, and more preferably less than 160 mPa·s, and a viscoelastic coefficient of less than 14, and more preferably less than 13. The liquid crystal composition of the present invention comprises a first component and a second component which use an isothiocyanate liquid crystal substituted with meta-position fluorine. Compared with the isothiocyanate liquid crystal substituted with ortho-position fluorine disclosed or already used in the prior art, the following surprising results are obtained: (1) lower rotational viscosity; (2) higher birefringence; (3) lower viscoelastic coefficient; and (4) higher clearing point. The liquid crystal compounds and compositions of the present invention can be used in liquid crystal optical devices, such as phase modulators, optical phased arrays, wavelength selective switches, etc. operating in the near-infrared band. The liquid crystal compounds and compositions of the present invention can also be used in liquid crystal high-frequency microwave components, such as holographic liquid crystal phased array antennas. DETAILED DESCRIPTION Unless otherwise specified, the scientific and technical terms and methods in this document are based on the understanding of ordinary technicians in the relevant fields or are implemented using existing relevant methods. The present invention is further described in detail below in conjunction with specific embodiments. The material components used in the following examples can be commercially available products, or synthesized according to existing published methods, such as the method described in the document "Synthesis, mesomorphic and optical properties of isothiocyanatotolanes. Liquid Crystals 2003, 30(2): 191-198". It should be noted that the detailed test methods for the physical properties and photoelectric properties involved in the present invention are as follows: (1) Liquid crystal phase transition temperature: Differential scanning calorimetry (DSC) was used: under nitrogen atmosphere, the heating (cooling) rate was set to 5°C / min. Polarized light hot stage method: Place the liquid crystal sample in a cross-polarized light microscope hot stage and set the heating rate to 2°C / min. Observe the texture image of the liquid crystal phase transition under a polarized light microscope to determine the liquid crystal phase state. (2) Birefringence (Δn): Using an Abbe refractometer, at a constant temperature of 25°C and a light source of 589 nm, the ordinary light (n o ) and extraordinary light (n e )’s refractive index. (3) Dielectric constant (Δε, 1KHz): Under constant temperature of 25°C, the liquid crystal is poured into a 20μm anti-parallel cell and tested using an LCR meter. Δε = ε ∥ -ε ⊥ , that is, the dielectric constant along the long axis of the molecule (ε ∥ ) and the dielectric constant along the molecular short axis (ε ⊥ ) is extrapolated to obtain the dielectric anisotropy value Δε. (4) Rotational viscosity (γ1): At a constant temperature of 25°C, liquid crystal is poured into a 20 μm antiparallel box. By applying voltage to the liquid crystal test box, the instantaneous current value Ip of the liquid crystal molecules deflected by the electric field is tested, and the rotational viscosity γ1 is calculated and extrapolated. (5) Elastic constant (K 11 , K 33 ): Under the condition of 25℃ constant temperature, the capacitance-voltage (CV) curve of liquid crystal is tested and K is obtained by fitting. 11 and K 33 . (6) Viscoelastic coefficient: The ratio of rotational viscosity to elastic constant, i.e. γ1 / K 11 or γ1 / K 33 . The relevant descriptions of the codes involved in the embodiments and comparative examples of this article are shown in the following Tables 1-3: Table 1 Physical parameters Table 2 Abbreviations of structural units in this paper Table 3 Examples of structural abbreviations Embodiment 1: The component structure, mass percentage and performance data of the liquid crystal composition of this embodiment are shown in Table 4 below. The test data in Table 4 show that the liquid crystal composition of Example 1 has a relatively high birefringence, an extremely low rotational viscosity, and an extremely low viscoelastic coefficient. Embodiment 2: The component structure, mass percentage and performance data of the liquid crystal composition of this embodiment are shown in Table 5 below. Table 5 The test data in Table 5 show that the liquid crystal composition of Example 2 has a relatively high birefringence, an extremely low rotational viscosity, and an extremely low viscoelastic coefficient. Embodiment 3: The component structure and mass percentage of the liquid crystal composition of this embodiment and its performance data are shown in Table 6 below. Table 6 The test data in Table 6 show that the liquid crystal composition of Example 3 has a relatively high birefringence, an extremely low rotational viscosity, and an extremely low viscoelastic coefficient. Embodiment 4: The component structure and mass percentage of the liquid crystal composition of this embodiment and its performance data are shown in Table 7 below. Table 7 The test data in Table 7 show that the liquid crystal composition of Example 4 has a higher birefringence, extremely low rotational viscosity, and an extremely low ratio of rotational viscosity to elastic constant. Embodiment 5: The component structure and mass percentage of the liquid crystal composition of this embodiment and its performance data are shown in Table 8 below. Table 8 The test data in Table 8 show that the liquid crystal composition of Example 5 has a higher birefringence, extremely low rotational viscosity, and an extremely low ratio of rotational viscosity to elastic constant. Comparative Example 1: This comparative example uses a known isothiocyanate liquid crystal compound substituted with a fluorine atom at the ortho position of the benzene ring to replace the isothiocyanate liquid crystal compound substituted with a fluorine atom at the meta position of the benzene ring in Example 2. The component structure, mass ratio and performance data of the liquid crystal composition are shown in Table 9 below: Table 9 Compared with the above-mentioned Example 2, Comparative Example 1 has the same composition mass ratio, and the only difference is the position of the fluorine atom substitution of the monomer liquid crystal compound. It can be seen from Tables 5 and 9 above that the clearing point Tni of Example 2 is 9.5°C higher than that of Comparative Example 1; the birefringence Δn of Example 2 is 0.05 higher than that of Comparative Example 1; the elastic constant K of Example 2 is 11 The rotational viscosity γ1 of Example 2 is 2.1 pN higher than that of Comparative Example 1; the rotational viscosity γ1 of Example 2 is 13.4 mPa·s lower than that of Comparative Example 1, with a decrease of about 10.3%; the viscoelastic coefficient (γ1 / K 11 ) is 4.5 lower than that of comparative example 1, with a decrease of 27%. This shows that the liquid crystal composition of the present invention has achieved an unexpected technical effect by adjusting the fluorine substitution position of the components: the performance of the liquid crystal composition has been greatly improved, exceeding the composition composed of the existing known liquid crystal compounds with similar structures.

Claims

1. A low viscosity, high birefringence liquid crystal composition, It is characterized in that The liquid crystal composition comprises 60 to 100% by mass of a compound selected from the group consisting of compounds represented by general formula I as a first component: Wherein: R is an alkyl group having 1 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, or a 3-butenyl group.

2. The liquid crystal composition according to claim 1, It is characterized in that The liquid crystal composition further comprises 0 to 30% by mass of a compound represented by the structural formula II as a second component: Where: R 1 It is an alkyl group having 1 to 7 carbon atoms, an alkoxy group having 1 to 7 carbon atoms, or an alkenyl group having 2 to 5 carbon atoms.

3. The liquid crystal composition according to claim 1, It is characterized in that The liquid crystal composition further comprises 0 to 30% by weight of a compound represented by the general structural formula III as a third component: Where: R 2 is an alkyl group having 1 to 7 carbon atoms or an alkoxy group having 1 to 7 carbon atoms; and Ring A is a cyclohexane ring or a benzene ring.

4. The liquid crystal composition according to claim 1, It is characterized in that The liquid crystal composition further comprises 0 to 30% by weight of a compound represented by the general structural formula IV as a fourth component: Where: R 3 is an alkyl group having 1 to 7 carbon atoms or an alkoxy group having 1 to 7 carbon atoms; Ring A is a cyclohexane ring or a benzene ring; n=0 or 1.

5. The liquid crystal composition according to any one of claims 1 to 4, It is characterized in that The liquid crystal composition further comprises 0.001% to 1% by mass of an additive, wherein the additive is selected from a hindered phenol antioxidant and / or a hindered amine light stabilizer.

6. The liquid crystal composition according to any one of claims 1 to 4, It is characterized in that The liquid crystal composition further comprises one or more chiral additives, and the mass percentage content of the one or more chiral additives is 0.01% to 1%.

7. The liquid crystal composition according to any one of claims 1 to 4, It is characterized in that The birefringence of the liquid crystal composition at 25° C. and 589 nm is greater than 0.

39.

8. The liquid crystal composition according to any one of claims 1 to 4, It is characterized in that The rotational viscosity of the liquid crystal composition is less than 180 mPa·s.

9. The liquid crystal composition according to any one of claims 1 to 4, It is characterized in that The liquid crystal composition has a viscoelastic coefficient of less than 14.

10. Liquid crystal optical elements, It is characterized in that The liquid crystal optical element comprises the liquid crystal composition according to any one of claims 1 to 4.

11. Microwave components, It is characterized in that The microwave component comprises the liquid crystal composition according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Liquid-crystalline medium and high-frequency components comprising same

    CN105368465A

  • Liquid-crystalline medium and high-frequency components comprising same

    CN107955630A